A re-examination of ellipticity corrections for seismic phases. Issue 3 (17th August 2022) - Russell, Stuart; Rudge, John F; Irving, Jessica C E; Cottaar, Sanne
SUMMARY: The Earth's ellipticity of figure has an effect on the traveltimes of seismic waves over teleseismic distances. Tables of ellipticity corrections and coefficients have been used by seismologists for several decades; however, due to the increasing variety and complexity of seismic phases in use, current tables of ellipticity coefficients are now outmoded and incomplete. We present a Python package, EllipticiPy, for the calculation of ellipticity corrections, which removes the dependence on pre-calculated coefficients at discrete source depths and epicentral distances. EllipticiPy also facilitates the calculation of ellipticity corrections on other planetary bodies. When applied to both Earth and Mars, the magnitudes of ellipticity corrections are of the order of single seconds and are significant for some seismic studies on Earth but remain negligible on Mars due to other greater sources of uncertainty.